CO2 Solubility in Electrolyte Solution of Potassium Carbonate with the Addition of Promotor Amines (MDEA-DEA/ PZ-DEA) at Various Temperatures - Saidah Altway; Kuswandi Kuswandi; Iqwal Zulfetra; Firda Nuharani (Journal of Engineering and Technological Sciences, 2016)
Carbon dioxide has a huge impact on the increase of greenhouse gas formation causing global warming and climate change. The most effective method to capture CO2 is chemical absorption using potassium carbonate (K2CO3) solution and amines as additive to enhance the absorption rate. CO2 solubilities in 30% of K2CO3 and 5% of the total composition of mixed methyldiethanolamine (MDEA)"“diethanolamine (DEA) / piperazine (PZ)-DEA solutions at various temperatures of 303.15-323.15 K and atmospheric pressure are reported. The solubility data were measured using an equilibrium cell apparatus with the N2O analogy method. The E-NRTL model was used to correlate the experimental data accurately. The binary interaction parameters of the model for the CO2-K2CO3-MDEA-DEA-H2O and CO2-K2CO3-PZ-DEA-H2O systems were obtained. The CO2 physical solubility in 30% of K2CO3, 5% of PZ, and 0% of DEA at 303.15 K had the highest value, while the Henry constant of CO2 in this solution had the lowest value. The CO2 loading increased with increasing partial pressure of CO2, while the CO2 solubility decreased with increasing temperature. Any increase in MDEA concentration from 0% to 5% enhanced the CO2 partial pressure, otherwise, an increase in PZ concentration from 0% to 5% decreased the CO2 partial pressure.